ANALISIS PERAN PENDIDIKAN KEWIRAUSAHAAN DAN ILMU BISNIS DI SEKOLAH AL ATSAR ISLAMIC ENTREPRENEUR SCHOOL SOLO TERHADAP PENCIPTAAN WIRAUSAHA BARU - Dwi Suryanto; Untung Sunaryo; Moh.Luthfi (UNISAN JURNAL, 2025)
Entrepreneurship education at Al Atsar School focuses on developing students' business skills by integrating Islamic values into the entrepreneurship curriculum. This curriculum combines theory and practice, allowing students to design and run their own businesses. Key topics taught include business planning, marketing, financial management, and business development strategies, with an emphasis on business ethics and social responsibility aligned with Islamic principles. This hands-on learning approach has proven effective in fostering students’ entrepreneurial spirit, providing them with real-world experience in overcoming business challenges. Additionally, the role of teachers as mentors and the infrastructure support provided by the school accelerate the development of student businesses. Although challenges such as limited capital and practical experience exist, the entrepreneurship education at Al Atsar School has successfully created a number of ethical entrepreneurs ready to contribute to society.